Before and after the K/Pg extinction in West Antarctica: New marine fish records from Marambio (Seymour) Island - Cione, Alberto Luis; Santillana, Sergio Nestor; Gouiric Cavalli, Soledad; Acosta Hospitaleche, Carolina Ileana Alicia; Gelfo, Javier Nicolás; López, Guillermo M.; Reguero, Marcelo Alfredo (Cretaceous Research)
An ichthyofauna recovered from the López de Bertodano Formation at Units 9 (uppermost Maastrichtian) and 10 (lowermost Danian) and the Sobral Formation (Danian), in Marambio (Seymour) Island in the James Ross Basin is described and analyzed herein. A review of previously described taxa based on the new material and several new fish records for the López de Bertodano Formation is provided, including the youngest record of Enchodus and the first Cretaceous evidence of Pachycormiformes. We also identify the first Paleocene fishes for the continent. The new information and the reinterpretation of previous Cretaceous records show that there was no decline in fish diversity until the Cretaceous–Paleogene (K/Pg) boundary in the area and extinction event appears to have been rapid. Finally, we find that the distribution of some chondrichthyans and teleosts in the James Ross Basin appears to be climatically determined. Fil: Cione, Alberto Luis. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Santillana, Sergio Nestor. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Gouiric Cavalli, Soledad. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Acosta Hospitaleche, Carolina Ileana Alicia. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Gelfo, Javier Nicolás. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: López, Guillermo M. Universidad ...